Veterinary Oncology - Killick, David; LeBlanc, Amy.; Buckley, Aoife; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Veterinary Oncology will aim to cover all aspects of cancer research and clinical management in veterinary medicine. It will focus on the diagnosis, treatment, and prevention of cancer in various animal species, including but not limited to dogs, cats, horses, food animals, wildlife and exotic/zoo animals. The journal will welcome original research articles, reviews, case reports, and clinical studies that contribute to advancing knowledge in veterinary oncology. Topics of interest include cancer biology, tumor pathogenesis, novel therapies, diagnostic techniques and palliative care. We expect high welfare and ethical standards to be observed in all submitted work and that all relevant legislation and professional guidelines should be followed.
Keywords: Oncology; Veterinary medicine; Veterinary medicine; Oncology; Veterinary Science; Veterinary Clinical Medicine